Pengaruh Minat Belajar, Kecerdasan Emosional dan Motivasi Berprestasi terhadap Kemampuan Berpikir Kritis Fisika Peserta Didik Kelas XI UPT SMAN 4 Bantaeng - Marwati; Jasruddin; Kaharuddin Arafah (Postgraduate, University of Mataram, 2024)
This research is an experimental research with the type of Ex Post Facto research, which aims to analyze the effect of learning interest on achievement motivation, learning interest on critical thinking skills, emotional intelligence on achievement motivation, emotional intelligence on critical thinking skills. Using a casual survey method with Path Analysis techniques. Based on the results of expert assessments, it is declared valid and suitable for use. Furthermore, the instrument that was declared valid by the expert was then tested on class XII students, after the instrument was tested and a valid instrument was obtained, then the valid instrument was tested on class XI students. Based on the results of this study, it was obtained that the critical thinking skills of students in Physics were in the moderate category, while Learning Interest, Emotional Intelligence, and Achievement Motivation were in the high category. From the results of the Path Analysis test between variables, it was obtained that there was an insignificant influence of interest in learning Physics on achievement motivation, there was an insignificant influence between interest in learning on critical thinking skills, there was a significant influence between emotional intelligence on achievement motivation, there was an insignificant influence between emotional intelligence on critical thinking skills, there was an insignificant influence between achievement motivation on critical thinking skills.